Psychological and Social problems among first year B. Sc. Nursing students in selected institutions of Pune City - Sevak, Sanjay (Indian Journal of Nursing Sciences, 2024)
Campus life is not all new friends, parties and updating facebook status but many students struggle with major psychological and social problems in an unfamiliar environment. The present study was aimed to assess psychological and social problems among first year B. Sc. Nursing student in selected nursing institutes of Pune city. A total of 200 first year B. Sc. Nursing students from different nursing colleges of Pune city participated in study. The data collected through psychological and social structure questionnaires. The study reveals that students face various kinds of psychological and social problems. Thus, problems may result from being separated from home for the first time, the transition from a personal to an impersonal academic environment, overburdened by studies and assignments, having no one to share problems, difficulty in communication and difficulty in making friends significantly changes in classmates, seniors and living conditions. In some cases college students use several stress-relief measures to cope with their classes and assignments, ranging from smoking to alcohol consumption. Study reveals that students face various psychological and social problems whereas majority were able to manage this by support system, periodical guidance and counseling during first year B. Sc. Nursing course.